Do match officials give preferential treatment to the strongest football teams? An analysis of four top European clubs - Audrino, F. (Journal of Quantitative Analysis in Sports, 2018)
The fiercely debated question of whether the strongest European football clubs get special, preferential treatment from match officials in their decisions on the teams` players over the course of the teams` trophy winning streaks. To give an empirical answer to this question, we apply a rigorous econometric analysis for causal effect estimation to a self-constructed data set. We consider the two clubs in the Italian Serie A that experienced a prolonged winning streak during the period 2006-2016, namely Internazionale Milan (Inter) and Juventus Turin, as well as one team from the German Bundesliga (Borussia Dortmund) and one from the English Premier League (Manchester United) that also experienced a winning streak during the same period. This allows us to perform an analysis with enough statistical power to be able to estimate properly the effect of interest. The general opinion among fans, sports journalists, and insiders that the strongest clubs are favored by match officials` decisions is supported only by the results of the analysis we run for Juventus, whereas for the other clubs under investigation, we did not find any significant bias. During its winning streak, more yellow cards and total booking points (an aggregated measure of yellow and red cards) were given to Juventus opponents. These effects are not only statistically significant, but also have a sizeable impact.